(3QjGV GdeSGFd aj HjGf CMcGe GdTQY HGdOdGFds - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3cJGH GdYJb(B: (3hgh dZI GdNdhU, hefg Sej GdHJ YJbG dNdhUg ef CjOj GdLHGHQI(B...s
(3BNQgG (B:s
(3eY JeGe GdJMbjb aj GdeSCdI aj BNQ GdfXQ GdChd ef GdCQHYI ef cJGH GdOjGJ ef CQGO adjQGLY(B. (3KeI GdKGdKI JYbd GdYGbdI ddEfSGf LfGjI HJgeI dg Ydi EfSGf hEf cGfJ LfGjJgG eVehfI(B... (3agPG eG ChQOfGg hbUOfGg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B519s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B603s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis